TINJAUAN PENYEBAB DUPLIKASI PENOMORAN REKAM MEDIS ELEKTRONIK MENGGUNAKAN DIAGRAM FISHBONE DARI FAKTOR SUMBER DAYA MANUSIA GUNA MENINGKATKAN PELAYANAN MUTU PENDAFTARAN DI RUMAH SAKIT “X” - Trianto, Wowo; Cahyati, Amelia Devi (Jurnal TEDC, 2024)
Based on preliminary studies conducted by the author, it was found that there was a duplication of electronic medical record numbering, consisting of officers and patients. This study aims to determine the causes of duplication of electronic medical record numbering from human resource factors, knowing the numbering system, the impact of duplication of numbering and efforts made to prevent duplication of numbering that can affect the patient's health service process. The research method used was a descriptive method with a qualitative approach. The research subjects were the head of medical records, outpatient registration officers and storage officers. The object of research is duplicated patient medical record data and systems. Data collection techniques were observation, interview, documentation study, and literature study. The results of research related to duplication of electronic medical record numbering from human resource factors show that the obstacles are because officers have other workloads, officers are less careful in identifying, the length of work of officers affects performance and experience in overcoming problems, the education of outpatient registration officers is already with a D3 medical record background except for emergency registration, there are procedures that are abandoned when the data is incomplete. From the patient, including patients who do not bring complete requirements, elderly patients, accident/emergency patients, patients are impatient in waiting for the queue. The author suggests a more balanced division of workload and better organization of working hours so that officers can work carefully and efficiently.  Officers should remind elderly patients and give an appeal for the registration process to be accompanied by other children / guardians.